G07 Differences between Huntington's disease and spinocerebellar ataxia types 1 and 2 on cognitive and behavioural profile. (16th November 2010) - Soliveri, P; Mariotti, C; Paridi, D; Monza, D; Tomasello, C; Panzeri, M; Taroni, F; Albanese, A; Girotti, F
Abstract : Background: Huntington's disease (HD) patients show progressive, mostly frontal-striatal-type, cognitive deterioration, and heterogeneous psychiatric symptoms. In a previous study, we found that negative psychiatric symptoms were common in HD. Like HD, spinocerebellar ataxias (SCAs) are adult onset dominantly transmitted triplet expansion neurodegenerative diseases that affect cognition and behaviour, although these aspects have not been exhaustively explored. Aims: To compare cognitive and psychiatric impairment in HD and the two most common SCA forms in Italy (types 1 and 2). Methods: We examined 15 HD, 15 SCA1 and 15 SCA2 patients of similar age and education. We assessed functional invalidity with the Total Functional Capacity scale. To assess cognitive state we used: Raven Progressive Matrices for non-verbal deductive reasoning; the Short Tale Test for long term verbal memory; the Phonemic Fluency Test for strategic search for words; the Visual Search Test for focused attention; and the Benton Visual Orientation Line Test for orientation and spatial perception. We examined anxiety and depression with the Hamilton Rating Scales for Anxiety and Depression. The Scales for the Assessment of Positive and Negative (SANS) Psychiatric Symptoms were also used to assess schizophrenia-like symptoms. Results: HD patients did worse than SCA1 patients on most cognitive tests, except focused attention, where the two groups performed similarly. SCA2 patients had similar compromise to HD patients on most cognitive tests except verbal fluency, where HD did worse. The three groups did not differ on anxiety, depression or SAPS score but HD patients had a higher Scales for the Assessment of Positive and Negative score. Conclusions: Although cognitive impairment is greatest in HD, the impairment pattern in all three diseases is consistent with frontal-striatal dysfunction. However, the greater prominence of negative psychiatric symptoms in HD constitutes a clear difference compared with the similarly invalidating SCAs, also characterised by frontal-striatal dysfunction. The difference may be due to differing involvement of the frontal-striatal and cerebellar-striatal circuits in these conditions.